Effect of mammographic service screening on stage at presentation of breast cancers in Sweden - SW Duffy; Chien‐Jen Chen; RA Smith; Håkan Jonsson; Per Lenner; Lennarth Nyström; Sven Törnberg; Jan Frisell; Lars Holmberg (2007)
Previous results have shown a reduction in mortality with service screening in Sweden on the order of 40%. If the rate of tumors at a later stage were similarly reduced, this would give further support to the mortality findings.The rates of lymph node-positive cancers, of tumors >2 cm in pathological size, and of tumors of TNM stage II or worse before and after the introduction of screening were compared in 13 areas in Sweden, adjusted for changes in overall incidence during the period of study and stratified by age (40-49 and 50-69 years).Data were obtained on a total of 23,092 cancers and 10,177,113 person-years of observation. In women exposed to screening in the screening epoch, there was a significant 45% reduction in tumors of size >2 cm compared with the prescreening (relative risk [RR]=0.55, 95% confidence interval [CI]: 0.46-0.66) in the 40-49 age group, and a 33% reduction in the 50-69 group (RR=0.67, 95% CI: 0.62-0.72). For lymph node-positive and stage II+ disease, there were smaller but still significant reductions. No reduction in incidence in later-stage disease was observed in the unexposed women in the screening epoch.Screening has significantly and substantially reduced the rates of larger tumors and lymph node-positive breast cancer in Sweden, and the magnitude of the reduction is consistent with the reduction in breast cancer mortality.